2015
DOI: 10.1007/978-3-319-23525-7_29
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Unusual Crowd Events from Mobile Phone Call Detail Records

Abstract: The pervasiveness and availability of mobile phone data offer the opportunity of discovering usable knowledge about crowd behaviors in urban environments. Cities can leverage such knowledge in order to provide better services (e.g., public transport planning, optimized resource allocation) and safer cities. Call Detail Record (CDR) data represents a practical data source to detect and monitor unusual events considering the high level of mobile phone penetration, compared with GPS equipped and open devices. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
(38 reference statements)
1
33
0
Order By: Relevance
“…Thus the raw CDR data has space and time sparseness. Different techniques have been reported in the literature to identify user location and trajectory accurately which eventually reduces the space-time sparsity of the data [5], [49], [70].…”
Section: A Mobile Phone Network Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the raw CDR data has space and time sparseness. Different techniques have been reported in the literature to identify user location and trajectory accurately which eventually reduces the space-time sparsity of the data [5], [49], [70].…”
Section: A Mobile Phone Network Data Analysismentioning
confidence: 99%
“…To identify user's location, Dong et al defined that each user belongs to a cylindrical cluster with a certain existence probability [5]. Gonzalez et al considered the users to be concentrated at the centroid of the cell area [32].…”
Section: A Mobile Phone Network Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…CDR data have also been used to detect unusual urban events (e.g., elections, emergency events, etc. 16,17 ). Previous works on anomaly detection in transportation have looked at varied aspects of the problem including the detection of and finding the root causes of the anomalies.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, there has been an increasing interest in exploring both the temporal and spatial dimensions in social media data to extract and understand events at different spatial-temporal scales (Chen & Roy, 2009;Dong, Mavroeidis, et al, 2015;Rattenbury, Good, & Naaman, 2007). Mobile phone data have also been widely used in urban activity monitoring (Calabrese et al, 2010;Ratti, Frenchman, Pulselli, & Williams, 2006), event detection (Candia et al, 2008;Dong, Pinelli, et al, 2015;Traag, Browet, Calabrese, & Morlot, 2011), population density mapping (Deville et al, 2014), and tourism management (Ahas, Aasa, Mark, Pae, & Kull, 2007;Ahas, Silm, Järv, Saluveer, & Tiru, 2010). A more complete review on mobile phone data analysis can be found in Calabrese, Blondel, and Ferrari (2014).…”
Section: Re Late D Workmentioning
confidence: 99%